2005
DOI: 10.1016/j.gca.2005.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemistry of disordered mackinawite (FeS)

Abstract: Abstract-Disordered mackinawite, FeS, is the first formed iron sulfide in ambient sulfidic environments and has a highly reactive surface. In this study, the solubility and surface chemistry of FeS is described. Its solubility in the neutral pH range can be described by K s app ϭ {Fe 2ϩ } · {H 2 S(aq)} · {H ϩ } Ϫ2 ϭ 10 ϩ4.87Ϯ0.27 . Acid-base titrations show that the point of zero charge (PZC) of disordered mackinawite lies at pH ϳ7.5. The hydrated disordered mackinawite surface can be best described by strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
140
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(146 citation statements)
references
References 38 publications
5
140
0
1
Order By: Relevance
“…2), indicating the pH pzc of this synthetic amorphous FeS is pH 7.4 (±0.3, n = 3). This value is much higher than that reported by Widler (pH pzc = 2.9) [58], but consistent with the values reported by Wolthers (pH pzc = 7.5) [38]. Thus at pH >∼ 7.4, the surface becomes increasingly negatively charged, approaching saturation at high pH, while at pH <∼ 7.4, the surface becomes increasingly positively charged until the surface approaches saturation at pH 6.…”
Section: Potentiometric Titrationssupporting
confidence: 89%
See 2 more Smart Citations
“…2), indicating the pH pzc of this synthetic amorphous FeS is pH 7.4 (±0.3, n = 3). This value is much higher than that reported by Widler (pH pzc = 2.9) [58], but consistent with the values reported by Wolthers (pH pzc = 7.5) [38]. Thus at pH >∼ 7.4, the surface becomes increasingly negatively charged, approaching saturation at high pH, while at pH <∼ 7.4, the surface becomes increasingly positively charged until the surface approaches saturation at pH 6.…”
Section: Potentiometric Titrationssupporting
confidence: 89%
“…A stock amorphous iron sulfide (FeS) suspension was prepared by mixing equal volumes (20 mL) of 1.0 M Fe(NH 4 ) 2 (SO 4 ) 2 and 1.0 M Na 2 S solutions at a constant rate of 0.5 L/min into a 2.0 L reaction vessel while stirring at 800 rpm under Ar [38]. The suspension was filtered using a 0.2 µm nylon filter to isolate the solid, which was then freeze-dried in a lyophilizer over 3-4 days.…”
Section: Fes Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…A direct precipitation mechanism between iron and sulfide species is also encountered in hydrothermal sulfide deposits associated with volcanic activity. Mackinawite is the first crystalline iron sulfide phase that is formed in aqueous systems (Wolthers et al 2005) and is a precursor in sedimentary pyrite (FeS 2 ) formation (Wang & Morse 1996). Recent studies have demonstrated that mackinawite is an important natural reductant in soils and sediments for organic and inorganic contaminants (Moyes et al 2000;Moyes et al 2002;Lee & Batchelor 2003;Arias and Tabo 2003;Livens et al 2004;Bruggeman et al 2005).…”
Section: Transport and Redox Reactionsmentioning
confidence: 99%
“…Mackinawite was reported as an effective isolating material for use as a sediment cap (Liu et al, 2009). Although pure mackinawite can immobilize mercury, it has a low stability when exposed to oxidized conditions (Burton et al, 2009;Liu et al, 2008;Wolthers et al, 2005). Under field conditions, the capping material has to be in contact with the oxigenated water column during the capping building.…”
Section: Introductionmentioning
confidence: 99%